2016
DOI: 10.1155/2016/5796305
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine (C‐X‐C) Ligand 12 Facilitates Trafficking of Donor Spermatogonial Stem Cells

Abstract: The chemokine (C-X-C) receptor type 4 (CXCR4) is an early marker of primordial germ cells (PGCs) essential for their migration and colonization of the gonads. In spermatogonial stem cells (SSCs), the expression of CXCR4 is promoted by the self-renewal factor, glial cell line-derived neurotrophic factor (GDNF). Here, we demonstrate an important role of CXCR4 during donor mouse SSCs reoccupation of the endogenous niche in recipient testis. Silencing of CXCR4 expression in mouse SSCs dramatically reduced the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
(58 reference statements)
3
12
0
Order By: Relevance
“…Requirement for a CXCL12-induced effect on the germ cell population is the expression of respective receptors on the cell surface of spermatogonia. For CXCR4, relevant studies have demonstrated that spermatogonia isolated via the cell surface receptor THY1, display higher expression levels of CXCR4 compared to testicular somatic cells (Oatley et al 2006, Niu et al 2016. More importantly even, CXCR4 protein was localized to the cell surface of spermatogonia residing along the basement membrane in testicular tissues from 3 and 5 days old as well as adult mice (Payne et al 2010, Chen et al 2015, Niu et al 2016.…”
Section: R214mentioning
confidence: 99%
See 1 more Smart Citation
“…Requirement for a CXCL12-induced effect on the germ cell population is the expression of respective receptors on the cell surface of spermatogonia. For CXCR4, relevant studies have demonstrated that spermatogonia isolated via the cell surface receptor THY1, display higher expression levels of CXCR4 compared to testicular somatic cells (Oatley et al 2006, Niu et al 2016. More importantly even, CXCR4 protein was localized to the cell surface of spermatogonia residing along the basement membrane in testicular tissues from 3 and 5 days old as well as adult mice (Payne et al 2010, Chen et al 2015, Niu et al 2016.…”
Section: R214mentioning
confidence: 99%
“…For CXCR4, relevant studies have demonstrated that spermatogonia isolated via the cell surface receptor THY1, display higher expression levels of CXCR4 compared to testicular somatic cells (Oatley et al 2006, Niu et al 2016. More importantly even, CXCR4 protein was localized to the cell surface of spermatogonia residing along the basement membrane in testicular tissues from 3 and 5 days old as well as adult mice (Payne et al 2010, Chen et al 2015, Niu et al 2016. Upon induction of meiosis (days 14 and 21 pp), expression of CXCR4 was also detected in differentiating germ cells as well as in spermatids and even interstitial cells in adult testes.…”
Section: R214mentioning
confidence: 99%
“…Therefore, there are two problems in repairing Leydig cell dysfunction with ADSCs: one is how to effectively induce ADSCs to migrate to the sites of Leydig cell dysfunction in the testes so that these cells can be regulated by the testicular microenvironment, and the other is how to improve the ability of ADSCs to differentiate into Leydig‐like cells after colonization of the testes. Zhiyv et al reported that the stromal cell‐derived factor‐1 (SDF‐1)/CXC chemokine receptor‐4 (CXCR4) pathway is the most important biological axis for promoting MSC homing to injured tissues and that MSCs positive for CXCR4 expression can migrate to injured tissues with the help of SDF‐1. However, in vitro MSC culture reduces CXCR4 expression and weakens this homing ability.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in this respect, TPCs significantly complement the roles of Sertoli cells in the formation of a functional spermatogonial stem cell niche. In addition, HTPCs secrete a plethora of factors including the chemokine C‐X‐C motif chemokine ligand 12 (CXCL12) (Flenkenthaler et al ., ), which also plays roles in the regulation of the SSC niche (Westernstroer et al ., ; Niu et al ., ), but is not well examined in the human testis (McIver et al ., ).…”
Section: Introductionmentioning
confidence: 99%